2013
DOI: 10.1590/s2176-94512013000400015
|View full text |Cite
|
Sign up to set email alerts
|

Long-term evaluation of apical root resorption after orthodontic treatment using periapical radiography and cone beam computed tomography

Abstract: PR showed more frequency of ARR in posterior teeth groups when compared with CBCT images. ARR did not change in long-term post treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
22
0
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 27 publications
0
22
0
4
Order By: Relevance
“…External resorption has been connected to a number of factors. However, it occurs mainly because orthodontic treatment is an irreversible condition that adversely affects tooth prognosis (19) .…”
Section: Discussionmentioning
confidence: 99%
“…External resorption has been connected to a number of factors. However, it occurs mainly because orthodontic treatment is an irreversible condition that adversely affects tooth prognosis (19) .…”
Section: Discussionmentioning
confidence: 99%
“…This tissue is then absorbed by macrophages, odontoclasts, and osteoclasts. If the hosts response to this infection is too active, these same cells absorb not only the necrotic tissue, but also root cementum, and even dentine (7). Mild to severe resorption is a side effect affecting between 12 % and 17 % of orthodontic patients, with 10 -20 % of these patients developing resorption of greater than 3 mm.…”
Section: Introductionmentioning
confidence: 99%
“…- 21 Farman and Scarfe16 reported that several CBCT systems may be used to obtain reconstructions similar to conventional cephalometric scans. According to these authors, 16 CBCT diagnostic precision and efficacy may be compared to conventional cephalometric imaging.…”
Section: Introductionmentioning
confidence: 99%